Scientific Literature in Sanskrit - Sarma, Sriramula Rajeswara; Wojtilla, Gyula (Papers of the 13th World Sanskrit Conference ;, 2011)
Papers presented at the 13th World Sanskrit Conference, held at Edinburgh during 10-14 July 2006.